Can the 3rd Hour Value of 100 g Oral Glucose Tolerance Test Be Ignored in the Diagnosis of Gestational Diabetes Mellitus? - Mehmet Metin Altay; Serdinç Özdoğan; Aytaç Tohma; Sertaç Esin; Okyar Erol; Orhan Gelişen; Melih Akkuş; Sinan Karadeniz (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To investigate whether the 3rd hour value of 100 g oral glucose tolerance test (OGTT) can be ignored when diagnosing gestational diabetes. STUDY DESIGN: During the first 8 months of 2010, 6909 patients between 24 and 28 weeks’ of gestation were screened with 50 g glucose challenge test and 140 mg/dl or higher plasma glucose levels were further evaluated with 100 g OGTT to diagnose gestational diabetes mellitus (GDM). 1195 patients’ test results were acquired for this retrospective study. For the 100 g OGTT fasting plasma glucose cut-off value was 105 mg/dl, 1 hour cut-off value was 190 mg/dl, 2 hour cut-off value was 165 mg/dl and 3 hour cut-off value was 145 mg/dl. Patients with 2 or more values above the cut-off level were diagnosed as GDM. RESULTS: Out of 1195, 124 patients (10.4%) were diagnosed as having GDM. 65 patients (52.4%) had high values of first and second hours; 33 patients (26.6%) had high values of first, second and third hours; 19 patients (15.4%) had second and third hours high values; 7 patients (5.6%) had first and third hours high values of 100 gr OGTT out of those 124 patients. CONCLUSION: 79% of the patients were diagnosed with first and second hour test results but 21% of the patients were diagnosed with blood glucose levels above the third hour cut-off level. Thus, considering the difficulties of 100 gr. OGTT, third hour values is of diagnostic value and cannot be ignored.